New methods in diagnostic and therapyInvasive and non-invasive fractional flow reserve index in validation of hemodynamic severity of intracoronary lesions - Wasilewski, Jarosław; Mirota, Kryspin; Hawranek, Michał; Poloński, Lech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
This review discusses visual and functional evaluation of the hemodynamic significance of the degree of stenosis in coronary angiography, with respect to the indications for revascularization. The concept of the coronary flow reserve is defined, and the theoretical assumptions of the invasive measurement of the fractional flow reserve (FFR) are presented. In the following part, the publication describes the basic steps of numerical stimulations in terms of computational fluid dynamics (CFD) in calculating the fractional flow reserve based on computed tomography (CT) coronary angiography (FFR CT ). The numerical FFR CT estimation in correlation with invasive measurements, as well as benefits deriving from FFR CT in the diagnosis of coronary artery disease, is presented in the example of the multicentre prospective DISCOVER-FLOW trial and the DeFACTO project. The CDF method enables to obtain hemodynamic significance of stenosis solely from the coronary anatomy vizualized by CT angiography. The calculation of FFR CT increases the diagnostic reliability of coronary flow reserve estimations. It contributes to the improvement in patients’ qualification for contrast coronarography. If the accuracy of FFR CT is confirmed in clinical practice, and the time required for computational processing is shortened, it may turn out that the algorithms of coronary heart disease diagnosis will be verified and it will be to a greater extent based on the CT results.